2017
DOI: 10.1136/bjsports-2017-097912
|View full text |Cite
|
Sign up to set email alerts
|

Tackling concussion in professional rugby union: a case–control study of tackle-based risk factors and recommendations for primary prevention

Abstract: Interventions that reduce the speed and acceleration of the tackler and reduce exposure to head-to-head contact would likely reduce concussion risk in professional rugby union.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
107
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(111 citation statements)
references
References 23 publications
(36 reference statements)
4
107
0
Order By: Relevance
“…The chances of a concussion were decreased when the tackler did not move before the tackle event; this result is in line with those of previous studies. 6,10 The risk of concussions 6 and the propensity to cause an HIA 10 were significantly greater among tacklers moving at higher speeds or accelerating. Therefore, we recommend that tacklers control their speed in the pre-contact phase, which results in a tackle characteristic that lowers the risk of concussions at the moment of contact.…”
Section: Factors Reducing the Likelihood Of The Tackler-related Conmentioning
confidence: 96%
See 1 more Smart Citation
“…The chances of a concussion were decreased when the tackler did not move before the tackle event; this result is in line with those of previous studies. 6,10 The risk of concussions 6 and the propensity to cause an HIA 10 were significantly greater among tacklers moving at higher speeds or accelerating. Therefore, we recommend that tacklers control their speed in the pre-contact phase, which results in a tackle characteristic that lowers the risk of concussions at the moment of contact.…”
Section: Factors Reducing the Likelihood Of The Tackler-related Conmentioning
confidence: 96%
“…[3][4][5] Recently, in rugby union, research on the inciting events leading to concussion and head injury assessment (HIA) has increased, 6-10 with a particular focus on tackling situations. 6,[8][9][10] The aforementioned studies assessed professional rugby union players, and it is considered that the results are unlikely to be applicable to nonprofessional cohorts included both youth and community cohorts. 6,9,10 Furthermore, since the HIA is applied to the only professional level, it is easily possible to collect the concussion data and video records compared with community level.…”
Section: Introductionmentioning
confidence: 99%
“…Research on inciting events leading to concussion and HIA with video records has progressed rapidly in recent years [14][15][16][17] . Previous research, targeting the European professional level, suggested there was a higher risk of concussion when the tackler accelerated into a tackle or had head contact with the ball-carrier's head 14,17) . Sobue et al showed that concussion occurred significantly more often during tackles with incorrect head positioning (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…While we accept that the removal of the tackle may be detrimental to the identity of rugby, the removal of tackling is likely to be the most effective injury prevention strategy in this particular instance 11. In contexts, such as the community game however, where children and their parents choose (expressed and informed consent) to participate in environments where coaches are expected to hold a rugby-specific qualification, we are not calling for the removal of tackling from the youth game.…”
Section: Cautionary Approachmentioning
confidence: 96%